Why do millennials still shop at department stores? - Atussolihah, Badi; Sari, Putu Ratna Juwita (Review of Management, Accounting, and Business Studies, 2023)
This study investigated the factors influencing purchasing decisions among millennials in the retail environment, with a focus on recent fashion, sales promotion, and store ambiance. Utilizing a quantitative research approach, data was collected from millennials residing in Denpasar City, Bali, through questionnaire distribution. Factor analysis was employed to analyze the data, revealing four key factors: recent fashion, sales promotion, exterior store ambiance, and interior store ambiance. The results indicated that while recent fashion trends may have had a minor negative impact on purchasing decisions, sales promotions played a significant role in driving consumer interest. Moreover, both exterior and interior store ambiance exerted a substantial influence on purchasing decisions, emphasizing the importance of creating visually appealing and welcoming retail environments. These findings underscored the need for retailers to adopt a holistic approach to marketing and merchandising strategies, balancing trendy offerings with strategic promotions and enhancing store ambiance to optimize consumer engagement and drive sales. Overall, this study provided valuable insights for retailers seeking to understand and cater to the preferences of millennial consumers in the competitive retail landscape.